Perbandingan Hasil Pemeriksaan Leukosit, Trombosit, Hemoglobin, dan NLR pada Pasien Sepsis dan Syok Sepsis di PICU RSUP Dr. M. Djamil Padang - Saldi, Aisyah Afiah Izzaty; Mariko, Rinang; Almurdi, Almurdi (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Sepsis and septic shock are global health problems with high morbidity and mortality rates. The ability to identify sepsis and septic shock with tools available in health facilities in Indonesia is an important step in reducing the morbidity and mortality of this disease. One of the tests that can be performed is a complete blood count such as the number of leukocytes, platelets, hemoglobin levels, and neutrophil-lymphocyte ratio (NLR). The costs incurred for complete blood counts are low and generally available in all health facilities. Methods This study is an analytical observational study with a cross sectional research design using medical record data of sepsis and septic shock patients in the PICU of RSUP Dr. M. Djamil Padang in 2020 - 2022. Univariate analysis is presented in the form of a frequency distribution table and bivariate analysis using the Chi Square test. Results The results showed that the most common diagnosis was septic shock (74.5%), male (57.5%), age under one year (38.3%), and death outcome (59.6%). Bivariate analysis found that there was a difference in platelet count between sepsis and septic shock (p=0.004) and there was a difference in NLR between sepsis and septic shock (p=0.024). Conclusions The conclusion of this study is that there are differences in platelet count and NLR between sepsis and septic shock patients in the PICU of RSUP Dr. M. Djamil Padang.